147 Synchronous Parathyroidectomy and Extended Thymectomy in Multiple Endocrine Neoplasia Type 1- a Case Report. (19th August 2022) - Robinson, D; Smith, A; Bille, A; Simo, R
Abstract: In recent decades there has been a significant advancement in the management of neuroendocrine tumours (NETs) associated with multiple endocrine neoplasia type 1 (MEN-1). Hormone excess accounted for 75% of all MEN-1 deaths, however since the introduction of hormone blocking medication, deaths in patients with MEN-1 are now predominantly due to the malignant effects of the tumours. Half of all MEN-1 related deaths are due to tumours that are difficult to diagnose, including thymic NETs. Complete surgical resection is the mainstay of treatment for MEN-1 associated thymic NETs. The case patient was a 49-year-old male who was being investigated for a 3-month history of symptoms consistent with hypercalcaemia. Initially a chest X-ray demonstrated a large anterior mediastinal mass. Further imaging revealed parathyroid lesions and a calcified lesion in the uncinate process of the pancreas. This combination of symptoms and radiological evidence raised the possibility of MEN-1 as the diagnosis. The lesions were biopsy-proven atypical carcinoid NETs and the patient later underwent simultaneous neck dissection for bilateral subtotal parathyroidectomy and a midline sternotomy for total thymectomy of the large mediastinal mass. Further testing revealed the pancreatic mass was another primary tumour and the patient is scheduled for excision of this. In addition, the patient is also being treated with Lanreotide alongside chemotherapy. Mutation of the MEN-1 gene was later confirmed on genetic testing. Due to the increase in mortality from neuroendocrine malignancy, it is becoming ever more important to understand how to manage multiple NETs from a surgical perspective.